Chester Alan Arthur papers - Arthur, Chester Alan, 1829-1886.
Correspondence, financial papers, scrapbooks, clippings, and other papers, chiefly 1870-1888. Subjects include Arthur's presidency, his service as collector of customs for the Port of New York, and the New York Republican State Committee. Correspondents include Campbell Allen, Chester Alan Arthur II, James Gillespie Blaine, George Bliss, Benjamin Harris Brewster, Benjamin Helm Bristow, Roscoe Conkling, Robert Graham Dun, Hamilton Fish, Frederick T. Frelinghuysen, Ulysses S. Grant, Charles Julius Guiteau, Wayne MacVeagh, Edwin D. Morgan, Frederick J. Phillips, James C. Reed, Julia I. Sand, Philip Henry Sheridan, John Sherman, William T. Sherman, and Kate Chase Sprague.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Includes copies of material related to Chester Alan Arthur from other collections in the Manuscript Division.
In part, transcripts and photocopies of original correspondence in the files of Dun and Bradstreet, inc.
President of the United States.
Collection material in English.
Keywords: Allen, Campbell -- Correspondence; Arthur, Chester Alan, -- 1864-1937 -- Correspondence; Blaine, James Gillespie, -- 1830-1893 -- Correspondence; Bliss, George, -- 1830-1897 -- Correspondence; Brewster, Benjamin Harris, -- 1816-1888 -- Correspondence; Bristow, Benjamin Helm, -- 1832-1896 -- Correspondence; Conkling, Roscoe, -- 1829-1888 -- Correspondence; Dun, Robert Graham, -- 1826-1900 -- Correspondence; Fish, Hamilton, -- 1808-1893 -- Correspondence; Frelinghuysen, Frederick T. -- 1817-1885 -- Correspondence; Grant, Ulysses S. -- 1822-1885 -- Correspondence; Guiteau, Charles Julius, -- 1841-1882 -- Correspondence; MacVeagh, Wayne, -- 1833-1917 -- Correspondence; Morgan, Edwin D. -- 1811-1883 -- Correspondence; Phillips, Frederick J. -- Correspondence; Reed, James C. -- Correspondence; Sand, Julia I. -- Correspondence; Sheridan, Philip Henry, -- 1831-1888 -- Correspondence; Sherman, John, -- 1823-1900 -- Correspondence; Sherman, William T. -- 1820-1891 -- Correspondence; Sprague, Kate Chase, -- 1840-1899 -- Correspondence; New York (N.Y.) -- Collector of the Port of New York; Republican Party (N.Y.). -- State Committee -- Correspondence; Customs administration -- New York (State) -- New York; New York (State) -- Politics and government; United States -- Politics and government -- 1881-1885.; Presidents -- United States